Financing Mediation on the Effect of Firm Size and Capital Adequatiacy on the Profitability - Desiana, Lidia; Africano, Fernando (Politeknik Negeri Sriwijaya, 2023)
This research aims to find out how financing mediation Effects firm size and capital adequacy on profitability in Sharia Commercial Banks for the 2016-2020 period. The population is 14 Sharia Commercial Banks with a sample of 7 BUS. The conclusion is that firm size has a negative and significant effect on financing. Meanwhile, Capital Adequacy does not affect Financing. The firm size does not affect profitability. And Capital Adequacy has a positive and significant effect on Profitability. Financing has a positive and significant effect on profitability. Apart from that, Financing can mediate the Effect of Firm size on Profitability, and Financing can mediate the Effect of Capital Adequacy on Profitability.